Analisis Kinerja Keuangan Untuk Mengukur Tingkat Kesehatan Perusahaan Manufaktur Sub Sektor Farmasi pada Bursa Efek Indonesia Periode Tahun 2018-2022 - Salikin, Muhammad Adi Salikin; Lestari, Baiq Anggun Hilendri; Kartikasari, Nungki (Fakultas Ekonomi dan Bisnis Unram, 2024)
The aim of this research is to analyze the company’s financial performance to measure the health level of pharmaceutical sub-sector manufacturing companies listed on the IDX in terms of liquidity, solvency, profitability and activity ratios for the 2018-2022 period. The sample used was 9 pharmaceutical sub-sector companies. The data analysis method used is quantitative descriptive. The research results show that the average ratio of liquidity, solvency, profitability and activity for pharmaceutical sub-sector companies fluctuates. Based on the liquidity ratio, Kimia Farma Tbk has the highest average value of the current ratio, Sido Muncul Herbal & Pharmaceutical Industry Tbk has a quick ratio and Indofarma Tbk has a cash ratio so it is classified as a company with the highest level of health. The solvency ratio in the debt to equity ratio and debt to asset ratio of the Sido Muncul Herbal & Pharmaceutical Industry Tbk has the lowest average value ratio, while the long-term debt to equity ratio of Darya Varia Laboratoria Tbk is classified as a company with the highest level of health. Tempo Scan Pacific Tbk’s profitability ratio has the highest average ratio value for net profit margin and return on assets and Pyridam Farma Tbk for return on equity so it is classified as a company with the highest level of health. The activity ratio in the inventory turnover ratio and the fixed asset turnover ratio of Darya Varia Laboratoria Tbk and Organon Pharma Indonesia Tbk in the total asset turnover ratio each have the highest average ratio values so they are classified as companies with the highest level of health.